2021
DOI: 10.3389/fspas.2021.719715
|View full text |Cite
|
Sign up to set email alerts
|

On the Impacts of Ions of Ionospheric Origin and Their Composition on Magnetospheric EMIC Waves

Abstract: Large numbers of theory and observation studies have been conducted on electromagnetic ion cyclotron (EMIC) waves occurring in Earth’s magnetosphere. Numerous studies have shown that accurately specifying the ions of ionospheric origin and their composition can greatly improve understanding of magnetospheric EMIC waves, specifically their generation, their properties, and their effects on the magnetospheric plasma populations. With the launch and operations of multiple recent missions carrying plasma instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…In spite of the variations in methodologies and data coverage, results from past statistical studies and our work are complementary. The EMIC wave spatial scales in different MLT sectors (e.g., Blum et al., 2017 ), along with patterns in EMIC wave occurrence rates as a function of L shell, MLT, and magnetic latitude (MLAT), result from the sources of ion anisotropy, ion pitch angle distributions, and the effects of the plasma composition in different regions (e.g., Foster & Erickson, 2021 ; Lee et al., 2021 ; Usanova, 2021 , Jun et al., 2021 ). In this section, we discuss some of these studies to place our results comparing the overall occurrence rates of EMIC waves and the occurrence rates of waves with rising tones into the broader context of EMIC waves throughout the magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the variations in methodologies and data coverage, results from past statistical studies and our work are complementary. The EMIC wave spatial scales in different MLT sectors (e.g., Blum et al., 2017 ), along with patterns in EMIC wave occurrence rates as a function of L shell, MLT, and magnetic latitude (MLAT), result from the sources of ion anisotropy, ion pitch angle distributions, and the effects of the plasma composition in different regions (e.g., Foster & Erickson, 2021 ; Lee et al., 2021 ; Usanova, 2021 , Jun et al., 2021 ). In this section, we discuss some of these studies to place our results comparing the overall occurrence rates of EMIC waves and the occurrence rates of waves with rising tones into the broader context of EMIC waves throughout the magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of these parameters are readily available for EMIC waves at L ≥ 3.0 thanks to high‐frequency magnetometer satellite observations and wave measurements, and have been included in electron diffusion models (Ross et al., 2020, 2021). However, the ion composition of the cold plasma also significantly affects the resonant interactions (Meredith et al., 2003) and the banded structure of EMIC waves (Lee et al., 2021). In particular, high ion fractions of the ion species of the EMIC wave band favor lower resonant energies (Albert, 2003; Summers & Thorne, 2003), while an increased fraction of heavier ions can restrict the frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction Ultra-low frequency electromagnetic ion cyclotron (EMIC) waves in the Pc 1-2 frequency range are a prominent feature of the magnetosphere-ionosphere (e.g., J. H. Lee et al, 2021;Usanova, 2021;Noh et al, 2022;Engebretson et al, 2021). Early theoretical work suggested that EMIC waves are transverse left-handed polarized waves generated near the magnetic equator by anisotropic protons (e.g., Cornwall, 1965); however, various polarizations, such as right-(RHP), lefthanded (LHP), and linear polarization, are also reported (e.g., Anderson et al, 1992;Min et al, 2012;Saikin et al, 2015;Allen et al, 2015).…”
Section: Plain Language Summarymentioning
confidence: 99%